Revisiting the Ganzfeld ESP Debate: A Basic Review and Assessment - Williams, Bryan (Journal of Scientific Exploration, 2011)
This paper presents a brief review of the debate between parapsychologists and skeptics regarding the issue of replication in experimental tests of extrasensory perception (ESP) using a sensory reduction technique known as ganzfeld. The review is followed by a basic assessment of 59 ganzfeld ESP studies reported in the period following the publication of a stringent set of methodological guidelines and recommendations by R. Hyman and C. Honorton in 1986. The assessment indicates that these 59 studies have a combined hit rate of approximately 30%, which is significantly above the chance expected hit rate of 25%. A comparison of the hit rates across four ganzfeld meta-analyses, as well as across fifteen laboratories, seems to further indicate replication of the ganzfeld ESP effect by a broad group of independent researchers. Keywords: extrasensory perception (ESP)—ganzfeld—meta-analysis—psi—parapsychology